Chemical characteristics of water in reservoir "Spilje" - Belichovska Katerina, Belichovska Daniela, Pejkovski Zlatko, Duraku Suzana (MIT University, Skopje, 2017)
Reservoir ‘Spilje” or Debar lake is located at the end of the Western part of Republic of Macedonia, around 5 km far from the city of Debar and it is one of the largest artificial lakes in the Republic of Macedonia. The lake has primarily been used as a source of energy, but, also, for fishing. Certain chemical characteristics of water from different locations of reservoir and different years has been investigated in this research. It was established that certain differences existed in chemical characteristics of water, depending on the location, as well as, on the period of the year when researches has been done. There were differences between summer and winter period, also. Significant differences in the presence of some cations and anions were established, related to the depth of water and the years, also, when investigation has been done. Starting from the surface towards the bottom of the lake, the values for Ca and SO4, show tendency of growing up, deeper than 20 meters of depth, but the values for Na and K, year by year, show tendency of declining.
Keywords: Reservoir „Spilje“, water, chemical characteristics.